A Novel SE-TCN-BiGRU Hybrid Network for Automatic Seizure Detection - Peilin Zhu; Weidong Zhou; Chao Cao; Guoyang Liu; Zhen Liu; Wei Shang (IEEE Access, 2024)
Automatic seizure detection plays a crucial role in epilepsy diagnosis and treatment. Traditional machine learning based automatic seizure detection requires additional feature engineering and finding the optimal hand-crafted features is a challenging issue. Therefore, a novel end-to-end deep learning model that combines attention mechanism, temporal convolutional network(TCN), and bidirectional gated recurrent unit (BiGRU) is proposed for seizure detection in this work. Our model only requires filtering of the raw electroencephalogram(EEG) signals to remove artifacts, without the need for time-consuming feature extraction. Post-processing procedures including moving-average filtering, thresholding, and the collar technique are then applied to enhance the model’s performance. Experiments were conducted on the CHB-MIT dataset and the SH-SDU dataset. In patient-specific experiments, our model achieved average accuracies of 98.77% on the CHB-MIT dataset and 93.61% on the SH-SDU dataset. In cross-patient experiments, average accuracies of 93.78% and 91.37% were obtained, respectively. The total time required for the model to process 1-hour EEG signals is only 5.33s. These outstanding results indicate that our model achieves high accuracy and real-time performance in seizure detection tasks and could provide reference for clinical seizure diagnosis.